Implementation of agile methodology in the development of human resource management application for pharmacies - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
This research aims to develop an effective human resource management (HRM) application for pharmacies using Agile methodology. The problem identified was the lack of HRM applications that fit the needs of pharmacies, as well as challenges in adapting to the health industry's rapidly changing needs and regulations. The methods used include data collection through literature review and interviews, application development using the Extreme Programming method, user acceptance evaluation through beta trials and surveys, and functional testing to ensure application quality. The results showed that the developed HRM application successfully achieved a user satisfaction level of 82%, with features that functioned as expected. This research contributes to the development of HRM applications that are responsive to change, improve the efficiency of human resource management in pharmacies, and ensure user satisfaction. This research also confirms that the Agile approach effectively produces software solutions that can provide significant added value to the healthcare industry.